1995
DOI: 10.1080/01635589509514370
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, weight gain, and risk of endometrial cancer

Abstract: Excess weight near the time of diagnosis is a well-established risk factor for endometrial cancer; less is known about the influence of weight at earlier periods of a woman's life or weight gain in adulthood. In a case-control study in western New York State, interviews were conducted with 232 incident endometrial cancer cases, diagnosed between 1986 and 1991, and 631 community controls. Body mass index at 16 years of age and 20, 10, and 2 years before interview and changes in body mass index between these tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 15 publications
5
43
0
Order By: Relevance
“…These discrepancies may relate to either varying definitions in obesity or to when in life obesity is considered. In the current study, there was little evidence of any variation in risks by follow-up time, suggesting that persistent obesity may be a more important predictor of risk than recent changes, in line with other observations (42)(43)(44). This notion was also supported by our finding of the highest uterine cancer risks being associated with younger ages of obesity diagnoses.…”
Section: Discussionsupporting
confidence: 81%
“…These discrepancies may relate to either varying definitions in obesity or to when in life obesity is considered. In the current study, there was little evidence of any variation in risks by follow-up time, suggesting that persistent obesity may be a more important predictor of risk than recent changes, in line with other observations (42)(43)(44). This notion was also supported by our finding of the highest uterine cancer risks being associated with younger ages of obesity diagnoses.…”
Section: Discussionsupporting
confidence: 81%
“…One study (19) showed that risk was greatest among those who fell into the highest category of BMI as a teenager (age 16 years) and subsequently gained the most weight during adulthood. Another study (23) reported that women who consistently weighed >10 lbs.…”
Section: Cancer Epidemiol Biomarkers Prev 2007;16(4) April 2007mentioning
confidence: 99%
“…Several studies reported a statistically significant (7,9,10,12,(19)(20)(21) or marginally significant (22) positive relation between adult weight gain and endometrial cancer risk, showing a 2-to 6-fold increased risk with increasing level of weight gain. Adult weight gain has not always been consistently defined in these studies but has generally encompassed weight gain from age 18 years to current ages.…”
Section: Cancer Epidemiol Biomarkers Prev 2007;16(4) April 2007mentioning
confidence: 99%
“…In obese women before the menopause it is probably primarily the lack of progesterone (because of ovarian androgen production and continuous anovulation) that may increase the risk of endometrial cancer, whereas after the menopause excess weight may continue to increase risk primarily through elevated plasma levels of bioavailable oestrogens in the absence of ovarian progesterone synthesis (see later) (65) . Adult weight gain, potentially a more important indicator of long-term energy balance, has been shown to be associated with increases in risk for endometrial cancer in a dose-dependent manner (102)(103)(104)(105)(106) . Some evidence that fat distribution may be important for endometrial cancer has emerged from studies that have looked at other measures of adiposity, including waist : hip ratio, waist: thigh ratio, subscapular skinfold and subscapular:thigh skinfold ratio.…”
Section: Obesity and Endometrial Cancermentioning
confidence: 99%